A novel experimental approach for the catalytic conversion of lignocellulosic Bambusa bambos to bioethanol - Souvik Kumar Paul; Amar Jyoti Das (Current Research in Microbial Sciences)
Bambusa bambos (B.B) biomass is cellulose rich lignocellulosic material, containing 47.49% cellulose, 17.49% hemicellulose, 23.56% lignin was used as a potential substrate for bioethanol production. The research paper investigates the use of B.B biomass as a substrate for bio-ethanol production through a two-phase catalytic conversion process. Four water-regulated regimes were identified to optimize the conversion of lignocellulosic biomass to biofuel precursors. The catalytic hydrolysis of B.B using CuCl2 was conducted for 10 hours at 110˚C, in aprotic ionic liquid (1-Butyl-3-methylimidazolium chloride) medium. The concentrations of glucose and 5-hydroxymethylfurfural (5-HMF) were measured while varying the amount of water addition. Water played a crucial role in the conversion of cellulose to glucose and 5-HMF by influencing product yields through the interplay of transport properties like heat conduction and viscosity. The highest glucose yield was achieved at 60.82% when operating at a water inclusion rate of 115.72 µL water/h for a duration of 6 hours at 110˚C. On the other hand, the maximum HMF yield was observed as 5.84% at water inclusion rate of 77.15 µL water/h for 5 hours at 110˚C. Yeast mediated glucose fermentation resulted in a bioethanol concentration of 5.5 mg/mL utilizing 15 mg/mL of catalytically produced glucose at a temperature of 30°C. After catalytic hydrolysis, the ionic liquid was also efficiently recycled for a sustainable economy.